2024
DOI: 10.3390/bios14030153
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Electrocardiogram on Electrode-Pair Locations for Wearable Devices: Computational Analysis of Amplitude and Waveform Distortion

Kiyoto Sanjo,
Kazuki Hebiguchi,
Cheng Tang
et al.

Abstract: An electrocardiogram (ECG) is used to observe the electrical activity of the heart via electrodes on the body surface. Recently, an ECG with fewer electrodes, such as a bipolar ECG in which two electrodes are attached to the chest, has been employed as wearable devices. However, the effect of different geometrical factors and electrode-pair locations on the amplitude and waveform of ECG signals remains unclear. In this study, we computationally evaluated the effects of body morphology, heart size and orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This could have significant consequences for patients with conditions like COPD, where oxygen saturation is a crucial monitoring parameter for treatment decisions. Another study by Sanjo et al [ 89 ] explored the impact of electrode placement on electrocardiogram (ECG) signal quality and diagnostic accuracy. Researchers demonstrated that deviations from the standard electrode placement protocol can alter ECG signal readings.…”
Section: Introducing the Rpm Usability Impact Modelmentioning
confidence: 99%
“…This could have significant consequences for patients with conditions like COPD, where oxygen saturation is a crucial monitoring parameter for treatment decisions. Another study by Sanjo et al [ 89 ] explored the impact of electrode placement on electrocardiogram (ECG) signal quality and diagnostic accuracy. Researchers demonstrated that deviations from the standard electrode placement protocol can alter ECG signal readings.…”
Section: Introducing the Rpm Usability Impact Modelmentioning
confidence: 99%